2020
DOI: 10.1021/acsabm.0c01355
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Brush-Grafted Nanoparticles Preferentially Interact with Opsonins and Albumin

Abstract: Nanoparticles find increasing applications in life science and biomedicine. The fate of nanoparticles in a biological system is determined by their protein corona, as remodeling of their surface properties through protein adsorption triggers specific recognition such as cell uptake and immune system clearance and nonspecific processes such as aggregation and precipitation. The corona is a result of nanoparticle–protein and protein–protein interactions and is influenced by particle design. The state-of-the-art … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Thus, it was recently shown that cyclic polymer brush shells on small iron oxide nanoparticles provide qualitatively and quantitatively improved colloidal stability and protection against the adsorption of human serum albumin compared to equivalent linear polymer brush shells. 32 , 37 , 38 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it was recently shown that cyclic polymer brush shells on small iron oxide nanoparticles provide qualitatively and quantitatively improved colloidal stability and protection against the adsorption of human serum albumin compared to equivalent linear polymer brush shells. 32 , 37 , 38 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was recently shown that cyclic polymer brush shells on small iron oxide nanoparticles provide qualitatively and quantitatively improved colloidal stability and protection against the adsorption of human serum albumin compared to equivalent linear polymer brush shells. 32,37,38 Cyclic polymers have previously been investigated for their thermal stability as micelles. Tezuka and co-workers described higher thermal stability of cyclic block copolymers compared to chemically identical linear ABA triblock copolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Responsive polymer brushes have been widely used in antibacterial, 33 antifouling, 34,35 surface wetting, 36,37 and biomedical materials. [38][39][40] Therefore, the fabrication of the polymer brushes is widely recognized as one of the most powerful tools to control the surface properties. 41…”
Section: Introductionmentioning
confidence: 99%
“… 29 The challenge of preventing this corona is highlighted by even very dense polymer brushes, which resist certain proteins (lyzosyme/transferrin) but selectively captured albumin and immunoglobulins. 30 The protein corona is hence of crucial consideration for any material, with cells ‘seeing’ this, rather than the underpinning nanoparticle itself, meaning the hard corona composition defines any interactions. 31 These proteins can be described as the hard (irreversibly bound) and soft (reversibly bound) corona.…”
Section: Introductionmentioning
confidence: 99%